Portable Magnetic Tracking Systems Exploiting Neural Networks and Space Mapping Modeling - Wang, Kai (My University, 2008)
The traditional approach of Magnetic Tracking Systems (MTS) utilizes approximate models and Parameter Extraction (PE) for Position and Orientation (P&O) determination. The approximate models give inaccurate P&O information outside the "constrained region". PE is an iterative, intensive process for P&O calculations, which limits the speed of the tracking process.
Our MTS approach aims at accurate real-time P&O tracking. We utilize Artificial Neural Networks (ANN) with PE functionality to carry out the computational task for real-time P&O tracking. We apply Space Mapping (SM) modeling afterwards for system calibration to improve the accuracy of P&0 determination
This thesis addresses a different approach for P&O determination. The main motivation of this work is to determine the P&O in a fast and accurate manner. It this work, we mathematically develop and experimentally implement our MTS for both 2-D and 3-D examples. The results show good match between our extracted P&O based on our MTS approach and the actual P&0 measured values.
Keywords: Electrical and Computer Engineering; Electrical and Computer Engineering